Migration policies and gender difficulties in the family reunifications - Hervías Parejo, Vanesa (Investigaciones Feministas (Feminist Research), 2015)
Through family reunification, immigrant women gain easier access to areas of social protection dispensed by welfare states such as employment entitlements, legal stay, benefits, career breaks, scholarships and grants. This empirical study, however, detects gender inequalities that are especially damaging to immigrant women in the exercise of the right to regroup due to the jobs they hold, the responsibilities in the private sphere, the invisibility in public spaces and personal, social and administrative obstacles imposed from the origin and host countries.